HUBUNGAN PENDIDIKAN SEKS DAN PAPARAN MEDIA PORNOGRAFI DENGAN PERILAKU SEKSUAL REMAJA DI SMA NEGERI 01 LEBONG SELATAN KABUPATEN LEBONG PROVINSI BENGKULU - Metha Fahriani (STIKes CHMK, 2019)
The problem of adolescent sexual behavior is very complex, if it is not provided with good efforts, adolescents who have limited knowledge and understanding of adolescents will find it difficult to control their sexual urges which can lead to unnatural sexual behavior. This study aims to determine the relationship of sex education and exposure to pornographic media with teenage sexual behavior in 01 Lebong Selatan State High School, Bengkulu Province. This research is analytical survey research, using Cross Sectional design. The population of this study were students of class XII of 01 South Lebong State High School in Bengkulu Province as many as 140 students. The sampling technique in this study used Proportional Random Sampling of 100 people. Data collection in this study uses primary data and secondary data. Data were analyzed using univariate and bivariate analysis with statistical tests Chi-square (c2) and contingency coefficient (C) statistics. The results of the study were obtained from 100 adolescents in 01 Lebong Selatan Public High School, Lebong Regency, Bengkulu Province. There were 90 respondents (86.4%) who did not have good teen sexual behavior, there were 79 respondents (68.2%) who received less education about sex education, there were 90 respondents (86.8%) exposed to pornography media, there was a significant relationship between sex education and adolescent sexual behavior in Lebong Selatan 01 Public High School, Lebong Regency, Bengkulu Province with a close relationship category, there was a significant relationship between exposure to pornographic media and behavior sexual adolescence at Lebong Selatan 01 Public High School, Lebong Regency, Bengkulu Province with a close relationship category. It is expected that related parties can increase education and counseling efforts about sex to avoid negative impacts and dangers of negative sexual behavior in adolescents. Keywords: pornography media, sex education, sexual behavior